Smart road paint and road signs with the ability to change colour at low temperature - Fernandes, F. (2016)
The alarmingly high recorded accident rate in recent years has received a considerable attention from the road authorities  resulting in stronger prevention campaigns. Irrespective of the meritorious efforts of relevant institutions, the number of victims due to accidents increases yearly. From theoretical training of drivers, the conditions of the roads and the culture of citizens are among some reasons that contribute to this endemic, that affect many families on daily basis. The weather conditions can be unpredictable, placing additional requirements on the vehicle and driver?s skills to handle with the vehicle and the environment. The presence of snow or ice on the road can make driving difficult. Wet snow can make muddy roads and can also build up in the vehicle wheel cavities affecting the driving ability. The horizontal and vertical road marking signs are two simple methods of visual alert for the state of road surface. In this work, we describe the use of a material colour layer sensor, applied on the road surface, which works due to the colour change of horizontal road markings, as a result of temperature change of pavement and ice occurrence. These road pavements as well as intelligent road signs will warn drivers the presence of ice patches, and thus, contributing to minimize the occurrence of accidents.